Irregular migration as a challenge for democracy / edited by Elżbieta Kużelewska, Amy Weatherburn, Dariusz Kloza. - Kużelewska, Elżbieta; Weatherburn, Amy; Kloza, Dariusz (European integration and democracy series ;, 2018)
"Immigration has emerged as the defining issue of our times. [...] The challenge that the immigration issue poses to the future of European democracy is real. Immigration itself is a genuine challenge, but the fundamental challenge that immigration brings to the fore is a domestic one, it is about fundamentally different political visions that cut through the citizenry of Europe's nation states. With that, it becomes critically important how these nation-states, through their democratic institutions, tackle immigration. [...] we need both the scholarly analysis and reflection presented in this volume, and we need informed political innovation within and between Europe's nation-states." - from the Foreword by Prof. Dr. Kristian Berg Harpviken, Peace Research Institute Oslo "[...] In result, Europe, to its series of recent big questions [...] had to add another one: migrants stand ante portas and what to do with them? [...] We have chosen to look at the extent to which the past, the present and the future of irregular migration to Europe relates to the foundational values and principles on which Europe has been built, namely democracy, the rule of law (Rechtsstaat) and the respect for fundamental rights. We focus on those people who seek in Europe various forms of help, motivated by war or other injustices in the places where they come from. [...] the main aim of our book was to join the voluminous professional and academic literature on migration and to offer a few modest suggestion in which direction Europe should go whenever irregular migrants stand ante portas." - from the Preface by the Editors "This is a timely and elaborate volume interested in the question to what extent the challenge of irregular migration poses a challenge to democracy. The authors approach this issue from different ethical, legal and political angles. They do not shy away from developing concrete recommendations as to what the European Union could do when faced with migratory pressures. Overall, therefore, a highly recommendable contribution." - Prof. Dr. Florian Trauner, Vrije Universiteit Brussel